2008
DOI: 10.31899/hiv2.1012
|View full text |Cite
|
Sign up to set email alerts
|

Repositioning postnatal care in a high HIV environment: Swaziland

Abstract: The Population Council is an international, non-profit, nongovernmental institution that seeks to improve the well-being and reproductive health of current and future generations around the world and to help achieve a humane, equitable, and sustainable balance between people and resources. The Council conducts biomedical, social science, and public health research and helps build research capacities in developing countries. Established in 1952, the Council is governed by an international board of trustees. Its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 12 publications
3
22
0
Order By: Relevance
“…In Palestine, a five-fold increase in postnatal care utilization was realized after the inception of health information on the importance and schedules of postnatal care during prenatal care visits [19]. Additionally, the present results agree with a previous study in Swaziland [10], which showed a dramatic increase in postnatal care visits within the first week after delivery due to active health worker participation in educating and scheduling mothers.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In Palestine, a five-fold increase in postnatal care utilization was realized after the inception of health information on the importance and schedules of postnatal care during prenatal care visits [19]. Additionally, the present results agree with a previous study in Swaziland [10], which showed a dramatic increase in postnatal care visits within the first week after delivery due to active health worker participation in educating and scheduling mothers.…”
Section: Discussionsupporting
confidence: 94%
“…The level of EPNC use was only 15.4% in the present study, confirming that EPNC remains highly neglected [3,9], poorly utilized [6], inadequately recognized [10], and is the weakest of all reproductive, maternal, and child health interventions [2]. However, the proportion was similar to the overall postnatal care utilization rate of 13% observed in most parts of Africa [3,9,14].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Providing clinic services that are youth-friendly Increased use of reproductive health service, including counselling and testing [41] Multi-country III A review of HIV prevention interventions among youth from 80 developing countries. provider training from 2006 to 2007 found that the proportion of HIV-positive postpartum women not wanting another child increased from 77% to 83% [38]. Provider training increased the proportion of women being asked about their preferred contraceptive method, from 32% to 82%, and receiving their preferred method, from 28% to 70%.…”
Section: Early Postpartum Visits That Include Fp and Hiv Information mentioning
confidence: 99%
“…Increased condom use, contraceptive use, HIV testing and treatment, reduced unintended pregnancy [38] Swaziland III One week postpartum visit for HIV-positive mothers, with provider training on FP.…”
Section: Early Postpartum Visits That Include Fp and Hiv Information mentioning
confidence: 99%